Optimization of p-GaN/InGaN/n-GaN Double Heterojunction p-i-n Solar Cell for High Efficiency: Simulation Approach. (10th April 2014) - Kushwaha, Aniruddha Singh; Mahala, Pramila; Dhanavantri, Chenna
Abstract : We have conducted numerical simulation of p-GaN/In0.12 Ga0.88 N/n-GaN, p-i-n double heterojunction solar cell. The doping density, individual layer thickness, and contact pattern of the device are investigated under solar irradiance of AM1.5 for optimized performance of solar cell. The optimized solar cell characteristic parameters for cell area of 1 × 1 mm 2 are open circuit voltage of 2.26 V, short circuit current density of 3.31 mA/cm 2, fill factor of 84.6%, and efficiency of 6.43% with interdigitated grid pattern.